Studies on the Isolation of Lipids from Mangrove Isolated Cyanobacterial Species - P. Devesh, B. Aishwarya and R. Gyana Prasuna (Nature Environment and Pollution Technology, 2022)
Cyanobacteria are an important source of food and a primary producer of the aquatic food chains. Cyanobacteria are universally photosynthetic, with a higher plant type of photosynthesis, a large number of those also have the pivotal character of nitrogen fixation. Phytoplankton is made up of mostly cyanobacteria and microalgae. The microalgae store food in the form of lipids and serve as the source of energy as well as lipids for the fish. The lipid content of the fish depends on the diet that they take, and some of the lipids like the omega 3 and omega 6 fatty acids are derived from specific microalgae, like the marine protists and dinoflagellates including Thraustochytrium, Schizochytrium, and Phaeodactylum. Cyanobacteria being nutritionally more independent with nitrogen and carbon fixing ability, are more economical to grow in bulk. Hence the present work was aimed to screen the high lipid-containing cyanobacteria for use as fish feed. Five different cyanobacterial isolates, originally obtained from the mangroves were used as the sample cyanobacteria. The mangroves are a unique and at the same time stressful ecosystem. The significance of choosing cyanobacteria from this area is to allow for the isolation of cyanobacteria with unique characteristics. It is known that microorganisms from harsh or unique environments have even more potential for developing special survival strategies and for the production of more secondary metabolites. These cyanobacteria from stress environments can grow in conditions where other cyanobacteria or microalgae do not survive well. The isolation of lipids was performed by different extraction methods and separation using different solvent compositions was performed. The standard growth and biochemical studies of the cyanobacteria were conducted, followed by the assessment of their lipid content and variability. Out of the five isolates, a higher number of lipids were observed in AS1-(1) and AS2-(2). Lipids were isolated in chloroform-methanol and three variations of TLC were used to separate the lipids. The three are the single mobile phase, two mobile phase systems, and 2D development solvent system. The separation of the lipids gave the best results with the two mobile phase system, in which two different mobile solvent mixtures were used sequentially. The isolates AS1-(1) and AS2-(2) exhibited higher lipids, hence they could be a potentially suitable candidate as a fish feed.